Synthesis of lab-in-a-pipette-tip extraction using hydrophilic nano-sized dummy molecularly imprinted polymer for purification and analysis of prednisolone. - Arabi, M.; Ghaedi, M.; Ostovan, A.; Wang, Shaobin (Academic Press, 2016)
A novel pipette-tip based on nano-sized dummy molecularly imprinted polymer (PT-DMIP) assisted by ultrasonication for the effective enrichment and analysis of prednisolone from urine samples was developed. The PT-DMIP cartridge was prepared by packing the dummy molecularly imprinted polymer at the tip of the micropipette. The polymerization used betamethasone (BM) as the dummy template, 3-aminopropyltrimethoxysilane (APTMS) as the functionalized monomer, tetraethyl orthosilicate (TEOS) as the cross-linker and aluminum ion (Al(3+)) as a dopant to produce Lewis acid sites in the silica matrix for metal coordinative interactions with the analyte. Compared to conventional solid phase extraction (SPE), the PT-DMIP is cost-effective, fast, and easy to handle, while the system is very approachable and reduces the consumption of toxic organic solvent. HPLC-UV analysis revealed successful applicability of the sorbent for highly efficient extraction of perdnisolone from urine matrices. The extraction recovery was investigated and optimum conditions were obtained using central composite design. Good linearity for prednisolone in the range of 0.22-220µgL(-1) with regression coefficients of 0.99 reveals high applicability of the method for trace analysis. Under the optimized conditions, the recoveries are 89.0-96.1 with relative standard deviations (RSD) of less than 9.0%.